2018
DOI: 10.1136/jnnp-2017-317879
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation predicts cognitive decline in patients with Alzheimer’s disease

Abstract: ObjectiveTo determine the ability of transcranial magnetic stimulation (TMS) in detecting synaptic impairment in patients with Alzheimer’s disease (AD) and predicting cognitive decline since the early phases of the disease.MethodsWe used TMS-based parameters to evaluate long-term potentiation (LTP)-like cortical plasticity and cholinergic activity as measured by short afferent inhibition (SAI) in 60 newly diagnosed patients with AD and 30 healthy age-matched subjects (HS). Receiver operating characteristic (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 40 publications
(25 reference statements)
3
41
0
Order By: Relevance
“…A considerable body of literature has historically shown that AD and DLB are characterized by a deficit in short latency afferent inhibition (SAI), a marker of sensorimotor integration that largely relies on cholinergic circuits, and FTD and DLB show a striking alteration in short interval intracortical inhibition and facilitation (SICI‐ICF), which substantially depend on GABAergic and glutamatergic circuits, respectively. These findings have prompted subsequent studies, which have suggested that a neurophysiological assessment might not be far from being ready to be translated from the experimental to the clinical setting . However, to further confirm TMS utility for the diagnosis of AD and other neurodegenerative dementias and to extend its use broadly, multicenter studies assessing the best combination of TMS measures, thus achieving the highest classification performance, are desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable body of literature has historically shown that AD and DLB are characterized by a deficit in short latency afferent inhibition (SAI), a marker of sensorimotor integration that largely relies on cholinergic circuits, and FTD and DLB show a striking alteration in short interval intracortical inhibition and facilitation (SICI‐ICF), which substantially depend on GABAergic and glutamatergic circuits, respectively. These findings have prompted subsequent studies, which have suggested that a neurophysiological assessment might not be far from being ready to be translated from the experimental to the clinical setting . However, to further confirm TMS utility for the diagnosis of AD and other neurodegenerative dementias and to extend its use broadly, multicenter studies assessing the best combination of TMS measures, thus achieving the highest classification performance, are desirable.…”
mentioning
confidence: 99%
“…These findings have prompted subsequent studies, which have suggested that a neurophysiological assessment might not be far from being ready to be translated from the experimental to the clinical setting. [26][27][28][29][30] However, to further confirm TMS utility for the diagnosis of AD and other neurodegenerative dementias and to extend its use broadly, multicenter studies assessing the best combination of TMS measures, thus achieving the highest classification performance, are desirable.…”
mentioning
confidence: 99%
“…Motta and coworkers ( in their JNNP paper1) used a non-invasive repetitive transcranial magnetic stimulation (TMS) protocol to evaluate brain plasticity in patients with Alzheimer disease (AD). More than 15 years ago, we showed for the first time that a TMS test based on coupling motor cortex stimulation with peripheral nerve stimulation, termed short latency afferent inhibition (SAI), can probe central cholinergic pathways in humans2 and reveal cholinergic dysfunction in patients with AD 3.…”
Section: Non-invasive Brain Stimulation Techniques Can Reveal Early Smentioning
confidence: 99%
“…Several studies confirmed these findings in the following years and showed that SAI may contribute to (1) diagnosis of other forms of cholinergic dementia such as dementia with Lewy bodies; (2) differential diagnosis of different forms of dementia that present with normal SAI such as frontotemporal dementia and vascular dementia; (3) identify patients with mild cognitive impairment with an increased risk to convert into dementia; (4) identify patients with AD responsive to acetylcholinesterase inhibitors, predicting long-term response to treatment after a single oral dose of the drug4 (see Cantone et al for a review) 5. Using repetitive TMS, Motta found a strong inverse correlation between the amount of long-term potentiation (LTP) (which can in some cases reverse into long-term depression) and AD progression 1. Interestingly, the effectiveness of LTP also correlates inversely with cerebrospinal fluid (CSF) levels of tau, which are thought to interfere directly with physiological mechanisms of neuronal synaptic plasticity.…”
Section: Non-invasive Brain Stimulation Techniques Can Reveal Early Smentioning
confidence: 99%
See 1 more Smart Citation